An efficient grid-connected solar PV system with a fault-tolerant mechanism to mitigate the voltage disturbances - N. Jayakumar; B. Devi Vighneshwari; V. Prema (Institute of Advanced Engineering and Science, 2026)
One of the most effective renewable energy solutions for long-term power generation is a solar photovoltaic (PV) system that is connected to the grid. However, power quality and system reliability can be significantly impacted by grid-side voltage disturbances such as sag, swell, and faults. To reduce voltage fluctuations and improve grid stability, this study proposes an effective fault-tolerant (FT) solar PV system coupled with a dynamic voltage restorer (DVR). The adaptive DVR-based control method, which dynamically injects compensatory voltages based on disturbance amplitude to ensure uninterrupted and distortion-free power delivery, is the feature that makes this study unique. MATLAB/Simulink is used to model and simulate the system to assess its dynamic response under fault, sag, and swell situations. IEEE 519 standards are met by the suggested design, which produces average total harmonic distortion (THD) values of 0.59%, 1.16%, and 1.55% for 50%, 100% sag/swell, and three-phase fault circumstances, respectively. This indicates that even in challenging grid situations, the DVR can sustain high-quality voltage profiles. For implementation in renewable-rich or weak grid networks, the suggested FT-DVR configuration provides a workable and affordable solution that guarantees better voltage regulation, less harmonic distortion, and increased operational dependability for upcoming smart-grid integration.